Low-Income Countries' BRIC Linkage : Are there Growth Spillovers? - Samake, Issouf (IMF Working Papers; Working Paper ;, 2011)
Trade and financial ties between low-income countries (LICs) and Brazil, Russia, India, and China (BRICs) have expanded rapidly in recent years. This gives rise to the potential for growth to spill over from the latter to the former. We employ a global vector autoregression (GVAR) model to investigate the extent of business cycle transmission from BRICs to LICs through both direct (FDI, trade, productivity, exchange rates) and indirect (global commodity prices, demand, and interest rates) channels. The estimation results show that there are significant direct spillovers while indirect spillovers also matters in many cases. Based on these results, we show that growing LIC-BRIC ties have significantly helped alleviate the adverse impact of the recent global financial crisis on LIC economies.